Assessing the impact of clinically relevant medicinal chemistry teaching: Learning gains from case study approach - Fernanda Domingues Lustoza; João Paulo S. Fernandes (Brazilian Journal of Pharmaceutical Sciences)
Abstract Considering the unique role of medicinal chemistry in the pharmacists’ formation, in this work we assessed the impact of medicinal chemistry teaching on the interpretation of a clinical situation using statistical and learning gain analysis. Lectures were conducted with or without medicinal chemistry information about the drugs involved, and pre and post-tests were applied. Pharmacy students (n = 35) were divided into two experimental groups (control and test) and presented with a case report selected from literature involving statin-related myopathy when a pre-test was applied. A lecture containing pharmacological information on statins was delivered to the students from the control group. In contrast, the test group received the same information, but medicinal chemistry elements of statins were inserted, and afterward post-test was applied. The scores from the pre-test and post-test were statistically evaluated and used to calculate Cohen’s d, Hake’s, and Dellwo’s G learning gains to compare the performance of the students from both groups. The results showed that students from the test group obtained significantly higher performance in the post-test and higher learning gain values. In summary, medicinal chemistry elements provided important knowledge to unveil the reported clinical situation and to provide skills for adequate drug selection to avoid statin-related myopathy.